ИНТЕРТЕКСТУАЛЬНЫЕ СВЯЗИ В ЖАНРЕ ЛИТЕРАТУРНОЙ СКАЗКИ - Сулейменова, Г.М. (My University, 2019)
Аннотация В данной статье рассмотрены интертекстуальные связи фольклорной и литературной сказок на различных уровнях текста сказки (словесном, структурном, композиционном) и определение роли интертекстуальности в формировании жанра литературной сказки. Abstract The article considers intertextual relationships between folklore and literary tales at different levels of text of the tales (verbal, structural, compositional) and definition of the role of intertextua- lity in formation of a genre of literary tales.
Intertextual Relations in the Genre of Literary Tales
Keywords: интертекстуальные связи; литературная сказка; дискурс; архитекстуальность; жанр; прототип; intertextual relations; literary tale; discourse; architextuality; genre; prototype